Proceedings of the 12th International Conference on Computer Supported Education 2020
DOI: 10.5220/0009582904760483
|View full text |Cite
|
Sign up to set email alerts
|

Remote Pair Programming

Abstract: Computing students often learn to program individually or in variously-sized groups whilst studying in computing laboratories and face-to-face classes. Previous research indicates that learning via pair programming can lead to students improving the quality of their programming, enhancing their programming skills and increasing their self-confidence when programming. Pair programming also is well established as a mechanism that supports peer learning and self-assessment for novice and more experienced students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Similarly, the distinctions between the learners who work "solo" and those working in pairs were made in a 2018 paper, contributing to the conclusion that programming knowledge, collaboration, and technical skills were further improved with a partnership [40]. According to Cheng and Lei [41] and Hughes et al [37], discussions between students allow them to gain more insights, play a role in communication with others, and increase their confidence. Additionally, this phenomenon reduces communication problems between students and lecturers while increasing students' achievements and the lecturer's adequate supervision.…”
Section: A Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the distinctions between the learners who work "solo" and those working in pairs were made in a 2018 paper, contributing to the conclusion that programming knowledge, collaboration, and technical skills were further improved with a partnership [40]. According to Cheng and Lei [41] and Hughes et al [37], discussions between students allow them to gain more insights, play a role in communication with others, and increase their confidence. Additionally, this phenomenon reduces communication problems between students and lecturers while increasing students' achievements and the lecturer's adequate supervision.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Several studies performed empirical research on pair programming effects in the computer field. Subsequently, Adeliyi et al [19] and Hughes et al [37] indicated that pair programming led to seven positive outcomes, including mutual encouragement, reciprocal supervision, correction, re-examination, mutual trust, self-confidence, and sharing of expertise.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…In a pilot project, a small number of students used Adobe Connect for Remote Pair Programming (RPP). Results indicated an increase in: ability to work in a team, confidence in solving problems, sensitivity in communication with others, initiative and self-assessment [3].…”
Section: Introduction and Related Workmentioning
confidence: 98%
“…RPP shares similarities with traditional colocated pair programming where the person typing the code (the driver) and the person watching that coding to spot any errors or ways to improve the code (the navigator) switch roles regularly. Optimally, both pair partners verbalize their thoughts, questions, and ideas (Hughes et al 2020). Pair programming, when done effectively, is known to improve code quality, communication, and coding skills of both pair programmers.…”
Section: Introductionmentioning
confidence: 99%